2022
DOI: 10.1007/s10681-022-03028-6
|View full text |Cite
|
Sign up to set email alerts
|

Dwarfing gene Rht24 does not affect Fusarium head blight resistance in a large European winter wheat diversity panel

Abstract: Reduced height (Rht) genes are widely used in modern wheat breeding although some confer higher susceptibility to Fusarium head blight (FHB) caused by F. graminearum and other species. Our objective was to test whether the recently identified Rht24b dwarfing allele has a neutral effect on FHB response as reported previously from a single mapping population when unrelated winter wheat cultivars were analyzed. We artificially infected a panel of 420 cultivars divided into four genotypic groups (Rht24a + Rht-D1a,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Herter et al ( 2018 ) evaluated segregating materials derived from a biparental cross between two German winter wheat cultivars, “Solitär x Bussard”, and demonstrated that Rht24b was not associated with FHB resistance. This was recently confirmed in a large European winter wheat germplasm by Miedaner et al ( 2022 ) who also found that Rht24b did not affect FHB resistance. Therefore, strategies to develop FHB-resistant varieties with semi-dwarfing alleles should reconsider the choice of such Rht genes.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Herter et al ( 2018 ) evaluated segregating materials derived from a biparental cross between two German winter wheat cultivars, “Solitär x Bussard”, and demonstrated that Rht24b was not associated with FHB resistance. This was recently confirmed in a large European winter wheat germplasm by Miedaner et al ( 2022 ) who also found that Rht24b did not affect FHB resistance. Therefore, strategies to develop FHB-resistant varieties with semi-dwarfing alleles should reconsider the choice of such Rht genes.…”
Section: Introductionsupporting
confidence: 59%
“…The combination of Rht-D1b and Rht24b was more frequent in our cultivars as previously reported within European wheat germplasm (Würschum et al 2017 ; Tian et al 2019 ). The similar FHB severity observed between Rht24b and genotypes with tall alleles (NoRht) is an indication that Rht24b did not affect FHB resistance (Herter et al 2018 ; Miedaner et al 2022 ). Similarly, our results also revealed that Rht24b did not significantly contribute to anther retention.…”
Section: Discussionmentioning
confidence: 90%
“…Short-strawed varieties may have higher concentrations of HT-2 and T-2 as they are nearer to the source of Fusarium inoculum at ground level, or there may be some genetic linkage between dwarfing genes and susceptibility to HT-2 and T-2-producing Fusarium species. Several studies have shown association between dwarfing genes Rht B1b and Rht D1b and susceptibility to Fusarium Head Blight in wheat (He et al, 2016), whereas no association has been demonstrated for the dwarfing gene, Rht24b (Miedaner et al, 2022). Genetic linkage has been demonstrated for F. graminearum (DON) susceptibility and Rht D1b in wheat (Srinivasachary et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies also confirmed that there were inconsistent genotypic responses with varying disease reactions in various crops across environments, including wheat for FHB reaction (Yan and Falk. 2002;Buerstmayr et al 2008;Kadariya et al 2008;Sandhu et al 2015;Sharma et al 2016;Parihar et al 2017;Miedaner et al 2022). Breeders want to specify genotypes with high yields as well as wide adaptation in the overall breeding program for the agronomic character.…”
Section: Discussionmentioning
confidence: 99%